Knowledge, attitude and practices among parents regarding food poisoning: a cross-sectional study from Palestine - Sa'ed Zyoud; Jawad Shalabi; Kathem Imran; Lina Ayaseh; Nawras Radwany; Ruba Salameh; Zain Sa'dalden; Labib Sharif; Waleed Sweileh; Rahmat Awang; Samah Al-Jabi (BMC, 2019)
Abstract Background Food serves as a vehicle for many pathogenic and toxigenic agents that cause food-borne diseases. Knowledge, attitude, and practices are key factors in reducing the incidence of food-borne diseases in food service areas. The main objective of this study was to evaluate knowledge, attitude, and practices related to food poisoning among parents of children in Nablus, Palestine. Methods A cross-sectional study was conducted in primary healthcare centers in Nablus district from May to July 2015. Data were collected using structured questionnaire interviews with parents to collect information on food safety knowledge, attitudes, and practices, alongside sociodemographic characteristics. Results Four-hundred and twelve parents were interviewed, 92.7% were mothers. The median knowledge score was 12.0 with an interquartile range (IQR) of 11.0-14.0. The median attitude score was 11.0 with IQR of 10.0-13.0, while the median practice score was 18.0 with IQR of 16.0-19.0. Significant modest positive correlations were found between respondents' knowledge and attitude scores regarding food poisoning (r = 0.24, p < 0.001), knowledge and practice scores regarding food poisoning (r = 0.23, p < 0.001), and attitude and practice scores regarding food poisoning (r = 0.30, p < 0.001). Respondents with a higher education level and who live in a city were the only factors significantly associated with higher knowledge scores (p < 0.05). Attitude improved as educational level increased (p < 0.05) and income level increased (p < 0.05). Those of female gender and employed were statistically significantly associated with higher satisfactory hygienic practices in relation to the prevention of food poisoning (p < 0.05). Conclusions Knowledge, attitude, and practices regarding food poisoning prevention are associated with each other and are affected by a complex interplay between socio-economic variables. The study highlights the need for health education programmes and general awareness campaigns that intend not only to enhance knowledge but also promote parents to practice food safety measures strictly and further strengthen their awareness level.